Electrospinning for tissue regeneration - Bosworth, Lucy A.; Downes, Sandra (Oxford ; Cambridge : Woodhead Pub., 2011)
Electrospinning is a simple and highly versatile method for generating ultrathin fibres with diameters ranging from a few micrometres to tens of nanometres. Although most commonly associated with textile manufacturing, recent research has proved that the electrospinning technology can be used to create organ components and repair damaged tissues. Electrospinning for tissue regeneration provides a comprehensive overview of this innovative approach to tissue repair and regeneration and examines how it is being employed within the biomaterials sector. The book opens with an introduction to the fundamentals of electrospinning. Chapters go on to discuss polymer chemistry, the electrospinning process, conditions, control and regulatory issues. Part two focuses specifically on electrospinning for tissue regeneration and investigates its uses in bone, cartilage, muscle, tendon, nerve, heart valve, bladder, tracheal, dental and skin tissue regeneration before concluding with a chapter on wound dressings. Part three explores electrospinning for in vitro applications. Chapters discuss cell culture systems for kidney, pancreatic and stem cell research. With its distinguished editors and international team of expert contributors, Electrospinning for tissue regeneration is a valuable reference tool for those in academia and industry concerned with research and development in the field of tissue repair and regeneration. Provides a comprehensive overview of this innovative approach to tissue repair and regeneration covering issues from polymer chemistry to the regulatory processExamines employment within the biomaterials sector, reviewing extensive applications in areas such as uses in bone, muscle tendon, heart valve and tissue regenerationExplores electrospinning for in vitro applications and discusses cell culture systems for kidney, pancreatic and stem cell research.
Part I. Fundamentals of Electrospinning: 1. Introduction to electrospinning / L. Wang and A.J. Ryan -- 2. Polymer chemistry / P. Christian -- 3. The electrospinning process, conditions and control / B. Robb and B. Lennox -- 4. Regulatory issues relating to electrospinning / A. Wilson -- Part II. Electrospinning For Tissue Regeneration: 5. Bone tissue regeneration / A. Bassi [and others] -- 6. Cartilage tissue regeneration / T. Hardingham -- 7. Muscle tissue regeneration / K.D. McKeon-Fischer and J.W. Freeman -- 8. Tendon tissue regeneration / L.A. Bosworth -- 9. Nerve tissue regeneration / C. Wang [and others] -- 10. Heart valve tissue regeneration / M. Simonet [and others] -- 11. Bladder tissue regeneration / S.C. Baker and J. Southgate -- 12. Tracheal tissue regeneration / F. Acocella and S. Brizzola -- 13. Dental regeneration / I.U. Rehman and A.S. Kahn -- Skin tissue regeneration / A. Subramanian, U.M. Krishnan and S. Sethuraman -- 15. Wound dressing / T.R. Hayes and B. SU -- Part III. Electrospinning For In Vitro Applications: 16. Cell culture systems for kidney research / L.A. Bosworh, S. Schuler and R. Lennon -- 17. Cell culture systems for pancreatic research / J.D.D. Wan, S. Downes, M. Dunne and K. Cosgrove -- 18. Cell culture systems for stem cell research / K. Meade, R.J. Holley and C.L.R. Merry.
Includes bibliographical references and index.
Keywords: Tissue engineering; Electrospinning; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Electrospinning; Tissue engineering; Tissue Engineering -- methods; Guided Tissue Regeneration